Taxonomy of Hylotribus Jekel (Coleoptera: Anthribidae, Anthribinae): new synonymies, combinations and type designations - Queiroz, Fernando Ávila; Elgueta, Mario; Mermudes, José Ricardo M. (Zootaxa, 2017)
The type material of six species of Anthribidae from Chile and one from Peru, originally described as Stenocerus Schoenherr and Stenorrhynchus Philippi & Philippi and later transferred to Hylotribus Jekel, was reexamined. These species are Stenocerus asperatus Blanchard, 1851, Stenocerus aspis Erichson, 1847, Stenocerus posticalis Philippi & Philippi, 1864, Stenocerus quadratipennis Germain, 1854, Stenorrhynchus quadrinotatus Philippi & Philippi, 1864, and Stenocerus tuberculosus Blanchard, 1851. Lectotype designations were made for Hylotribus asperatus, Hylotribus quadratipennis, and Hylotribus tuberculosus. New synonyms were established as follows: Hylotribus signatipes (Blanchard, 1851) = H. quadratipennis (Germain, 1854) syn. n., = H. quadrinotatus (Philippi & Philippi, 1864) syn. n., Hylotribus asperatus (Blanchard, 1851) = H. posticalis (Philippi & Philippi, 1864) syn. n.. While, Hylotribus aspis (Erichson, 1847) from Peru was transferred to Piesocorynus Dejean, 1834 and a new combination and synonymy proposed, Piesocorynus aspis (Erichson, 1847) n. comb. = Piesocorynus gracilicornis (Jekel, 1855) syn. n. The genus Hylotribus is defined with five species from Chile and six from Brazil, and the Chilean species are redescribed with illustrations. A new key to all species is included.